PERANAN PSIKOLOGI PENDIDIKAN SEBAGAI KOMPETENSI DASAR PENDIDIK DAN TENAGA KEPENDIDIKAN - SANJAYA, PUTU (Institut Hindu Dharma Negeri Denpasar, 2017)
Education is the interaction between educators and learners. Educational interactions are always related to knowledge, potential development, and the cultivation of values, either through the process of learning, guidance or training. In this interaction individuals behave, and behaviors into study materials of educational psychology. Thus the psychology of education is the study of a person's behavior (especially learners) in interacting with the educational environment. A teacher is obliged to understand the psychology of education, considering that teachers interact with students and also others, more often, in the educational process.